Assessing accounting disclosure by waqf institutions: A descriptive study through content analysis - Kadir M.R.A.; Sapuan N.M. (Science and Engineering Research Support Society, 2023)
Waqf is a voluntary, permanent, irrevocable dedication of a portion of ones wealth-in cash or in kind to God. Once the wealth is classified as waqf, it never gets gifted, inherited or sold. It belongs to God and the corpus of the waqf always remains intact. The fruits of waqf may be utilised for any shariah compliant purposes. Thus, it is important to ensure that waqf institutions are in good management. To prove their credibility, waqf institutions that handle waqf-related activities use accounting disclosures to provide their stakeholders with the sense of reliance and confidence on their operations. The purpose of this study is to examine the level of disclosure applied by waqf institutions in Malaysia. It intends to seek evidence on the accounting disclosure through waqf institutions annual reports based on the suggestions of Standard of Recommended Practice (SORP). Annual reports were collected from waqf institutions and analysed thoroughly using qualitative content analysis. The findings of this study show a mixed result on accounting disclosures of waqf institutions with variations of high, moderate and low disclosure levels. This study is expected to contribute to the improvement of disclosures by waqf institutions in Malaysia for the benefits of Muslim community as a whole. 2019 SERSC.